A Combine Spectrophotometric and Chromatographic Method Development and Validation of Levetiracetam Bulk And Tablet Dosage Form - Pimpale, Amol; Pagare, Rutuja; Aher, Smita; Phadtare, Dipti (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: Objective of the present analytical research work was to develop and validate Spectrophotometric method and High Performance Liquid Chromatographic method (HPLC Method) for the Levetiracetam bulk and tablet dosage form Methods: A spectrophotometric method and a HPLC method have been developed and validated for estimation of Levetiracetam in bulk. Method A (UV SPECTROMETRY Method): Methanol was used for the preparation of stock and working standard solutions of the drugs. 400-200nm UV range was used to scanned standard solutions of drugs using UV spectrophotometer. The λmax of Levetiracetam was found to be 220 nm. Method B (HPLC Method): The HPLC method for Levetiracetam was developed using cosmosil C18 (4.6 mm x 250 mm, particle size: 5 μm), as stationary particle, isocratic mode. Methanol: ACN: Water (60:20:20) pH3 as a mobile phase. The mobile phase was maintained at a flow rate of 1 ml / min and the detection was carried out at 220 nm. Both the methods were validated according to the ICH guidelines. Results: Levetiracetam was found to be linear in the concentration range of 10-50 µg/ml for spectrophotometric and HPLC method. Retention time was found to be 4.5 min for Levetiracetam. Interpretation and Conclusion: Results of validation study were found to be satisfactory. So, the methods can be successfully applied for the routine analysis of Levetiracetam.